Microanalysis of magnetic structure of yttrium-iron garnet films by using the scanning probe microscopy methods - Synhaivska, O.I.; Lytvyn, P.M.; Yaremiy, I.P.; Kotsyubynsky, A.O.; Kozub, V.V.; Solnstev, V.S.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
In this paper, the features of the microstructure of magnetic domains observed in ferrite-garnet films (FGF) have been presented. The studied FGF with orientation (111) were grown on gallium-gadolinium substrate by using liquid-phase epitaxy. The study of distribution inherent to magnetic domains was carried out using magnetic force microscopy (MFM) with the scanning probe microscope NanoScope IIIa Dimension 3000TM. In the course of these researches, optimization of the MFM method was carried out to obtain high-quality and correct images of magnetic domains in FGF. Nanorelief and magnetic microstructure of FGF surface were studied, depending on their thickness, on external magnetic field and doses of boron ion implantation. For these objects, it was established that stripe domain structure is characteristic, the period of which depends on the film thickness. The nature of transformation of domain structure depending on thickness is close to that theoretically predictable at low thicknesses (up to 10 µm). Nanorelief of film surfaces is virtually unchanged depending on thickness. An external magnetic field with the magnitude 4 mT causes significant changes in domain configuration and allows to visualize heterogeneity of magnetic structure. Ion implantation leads to a slight smoothing of nanorelief films (roughness of 0.2 nm) and to more accurate displaying the magnetic microstructure, which is associated with processes of structural ordering under ionic bombardment.